2016
DOI: 10.3390/molecules21081034
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen Metabolism by Adult Human Gut Microbiota

Abstract: Phytoestrogens are plant-derived polyphenols with a structure similar to human estrogens. The three main groups of phytoestrogens, isoflavones, ellagitannins, and lignans, are transformed into equol, urolithins, and enterolignans, respectively, by bacteria. These metabolites have more estrogenic/antiestrogenic and antioxidant activities than their precursors, and they are more bioavailable. The aim of this study was to analyze the metabolism of isoflavones, lignans and ellagitannins by gut microbiota, and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 64 publications
3
76
0
Order By: Relevance
“…Dihydrodaidzein was formed as an intermediate or a final metabolite by all but one of the tested microbiomes. This is in agreement with previous studies demonstrating the conversion of daidzein to dihydrodaidzein or genistein to dihydrogenistein in 70-90% of the human FS tested (Gardana et al 2009;Braune et al 2010;Gaya et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Dihydrodaidzein was formed as an intermediate or a final metabolite by all but one of the tested microbiomes. This is in agreement with previous studies demonstrating the conversion of daidzein to dihydrodaidzein or genistein to dihydrogenistein in 70-90% of the human FS tested (Gardana et al 2009;Braune et al 2010;Gaya et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…2 and 5) [64]. The unique catabolites include 4-hydroxy-mandelic acid from p-sympatol [65], tyrosols from oleuropein and related compounds [66], S-equol, 5-hydroxy-equol and dihydrocinnamic acids with the aryl residue at C2 formed from isoflavones [67,68], urolithins and nasutins from ellagitannins [69][70][71], diarylbutanes from lignans [32;35;36], and dihydroresveratrol from piceid and resveratrol [72]. The avenanthramides of oats, N-cinnamoyl conjugates of anthranilic acids, yield some unique catabolites, e.g.…”
Section: Conversion Of Polyphenols By the Gut Microbiotamentioning
confidence: 99%
“…Rodents fed with soy also showed less body weight [64]. Unfortunately, in this paper, the authors did not indicate the phytoestrogens bounded with the behavioral efect but reported high levels of equol in plasma, the more active metabolite of isolavones found in the soy [14].…”
Section: Preclinical Studiesmentioning
confidence: 53%
“…The extract from roots of rhubard mainly consists of rhaponticin and desoxyrhaponticin, which are converted to the resveratrol-like aglycones rhapontigenin and desoxyrhapontigenin by the microbiome. Rhapontigenin is more active than desoxyrhapontigenin, and it is suggested that P 450 -catalyzed O-demethylation giving the resveratrol-catechol piceatannol might be responsible for its estrogenic activity [14,55]. Clinical trials show that the rhubarb extract was efective and successfully decreased the Menopause Rating Scale and increased QoL [56][57][58].…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation